Emotional intelligence as a factor of achievement and social adjustment in early adolescence - Buško, Vesna (Array, 2007)
The study describes an attempt at operationalization of some of the proposed branches of emotional intelligence intended to assess these capabilities in early adolescents. An instrument aimed to assess the abilities of perception and regulation of emotions, composed in a form of objective performance test, will be presented, including the empirical data on its psychometric features. The study was conducted on a sample of 180 seven- and eight-grade primary school students. We examined the relationships of this instrument and several measures defined as peer-ratings of specific components of emotional intelligence postulated by Mayer and Salovey ability-based model (1997). By use of hierarchical multiple regression analysis we tested the relative importance of the stated indicators of emotional intelligence in explaining school achievement and sociometric status of primary school pupils. The results show that the regression equation including age and sex as general demographic features and emotional intelligence variables can account for approximately 39% and 56% of criterion variance, respectively. Ratings of the ability of verbal expression of emotions and, to the lesser extent, ratings of the conflict resolutions skills showed significant independent contribution to both criteria, whereas the role of the tests of emotional perception and emotional regulation within the predictor structure examined were found to be practically and statistically insignificant.